Compilação de dados de composição nutricional e quimiotaxonomia de espécies da família myrtaceae por UPLC-MS acoplada à quimiometria - Santos, Leonardo da Silva (2019)
Fruiting plants that belong to the Myrtaceae family have several genera and species spread throughout Brazilian biomes and exhibit plants with marked presence of secondary compounds belonging to various classes of medicines. It is still considered a complex family regarding taxonomic classification due to the number of superior components, difficult morphological difference and few studies in the area. The compilation of nutritional data is a systematic, quantitative review study of secondary data source. However, to enhance the classification and chemotaxonomic investigation in UPLC-QToF-MS / MS technique, obtain faster and more effective information compared to other techniques. This should affect the high selectivity and sensitivity of UPLC-QToF-MS / MS, which results in its application for both quantitative and qualitative analysis. Given the above, the present study deals with a systematic, quantitative review of secondary data source, aiming to contemplate an analysis of the nutritional composition of plant species from data measured in data using the compilation of values already used. As well as describe the potentiality of chemometric classification applied to UPLC-MS data for chemotaxonomic investigation of leaves of fifteen species of genus Psidium, Plinia, Myrciaria and Eugenia in the Myrtaceae family. A compilation was performed according to methodologies created by FAO / INFOODS. Fifteen plant species of the genus Psidium, Plinia, Myrciaria and Eugenia were studied. In the compilation, it is studied as native species or occurring in Brazil from researches of fruitful nutritional data in the published literature through databases, national and international scientific journals, master's dissertations and doctoral theses. Of the 10.308 scientific publications related to the research by scientific and popular name of the species, about 40 publications record nutritional composition data for the investigated fruits and approximately 11 publications used for data compilation. We found publications related only to fruits of jabuticaba, cambuí, guava, araçá-boi and pitanga according to the exclusion criteria. The identification of the nutritional composition of these foods increased the knowledge about biodiversity and nutritional composition of the studied fruits and encouraged the consumption, commercialization and development of new food products based on the species used. However, to give you a complete picture of their nutritional composition, more research in the area of food analysis is needed. In turn, the use of a multivariate tool was indispensable to detect markers, since the number of high information on chromatograms did not provide conclusive data. The results provide an appropriate gender and species classification, based primarily on magic acid, catechin, epicatechin, isoquercitrin, quercitrin, reynoutrine, madecassic acid, acid and moringa, used as marker agents. Therefore, the method was useful and allowed a satisfactory chemotaxonomic distinction between genders.